Life-Cycle Net Tax Rates and Intergenerational Redistribution: Evidence from Selected OECD Countries - Paolo Liberati (Luxembourg Income Study (LIS), 2000)
Using LIS data, this paper provides empirical evidence of how past tax/transfer policies in UK, US and Sweden have shaped both the intrapersonal and the intergenerational redistributive profiles. Measuring intrapersonal effects is important in order to disentangle life cycle inequalities and redistribution due to a non-linear age-income profile; while the estimation of intergenerational shifts could provide a more correct way to infer whether temporary static deviations of annual tax burdens have corresponding entries in a life cycle perspective. To this purpose, a cohort analysis is used, by which different samples of people belonging to the same generations are followed over time. Results are shown that over the last thirty years conventional cross-section inequality overestimates the true interpersonal effect of taxes and transfers in all countries, and that the true inequality reducing power of taxes and transfers is generally declining. Further, evidence of generational deviations from a common life cycle profile has been found, of different intensity and direction in the three countries considered, signaling the presence of intergenerational redistribution and its link with the pattern of fundamental tax reforms enacted in the observed period.
Keywords: 330; Intertemporale Einkommensverteilung; Overlapping Generations; Steuerbelastung; Großbritannien; Schweden; USA